Pengaruh Dosis Mikoriza dan Komposisi Media Tanam terhadap Pertumbuhan Bibit Kelapa Sawit di Pre Nursery - Roy Leonardo Lumban Batu; Suprih Wijayani; Pauliz Budi Hastuti (AGROISTA : Jurnal Agroteknologi, 2023)
The development of oil palm plantations begins with the procurement of quality seeds. This effort is carried out through the use of mycorrhizal fungi as biological fertilizers and and improvement of seedling planting media. This study aims to determine the effect of mycorrhiza dose with the mixed composition of rice husk charcoal and top soil on the growth of oil palm seedlings in the pre-nursery. This research was a factorial experiment arranged in a completely randomized design. The composition of the planting medium consists of four levels: top soil, 25% husk charcoal with 75% humus, 50% husk charcoal plus 50% top soil, and 100% husk charcoal solely. The dose of mycorrhizal biofertilizer consists of three levels, namely: 0.5 and 10 grams per seed. The results of this study indicated that the composition of the media or the application of mycorrhizal biofertilizers had no significant effect on the growth of oil palm seedlings in prenursery. The largest seedling leaf area was produced by seedlings planted on media containing husk charcoal which was given 10 grams of mycorrhizal biofertilizer.